2009
DOI: 10.1161/circulationaha.109.852202
|View full text |Cite
|
Sign up to set email alerts
|

Chest Compression Fraction Determines Survival in Patients With Out-of-Hospital Ventricular Fibrillation

Abstract: Background Quality CPR contributes to cardiac arrest survival. The proportion of time in which chest compressions are performed in each minute of CPR is an important modifiable aspect of quality CPR. We sought to estimate the effect of an increasing proportion of time spent performing chest compressions during cardiac arrest on survival to hospital discharge in patients with out-of hospital ventricular fibrillation or pulseless ventricular tachycardia. Methods and Results This is a prospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
399
5
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 680 publications
(421 citation statements)
references
References 30 publications
6
399
5
11
Order By: Relevance
“…Attempting to initiate ECMO during cardiac arrest is difficult as it requires pauses in CPR in order to cannulate and initiate the procedure. Prolonged CPR with periods without effective chest compressions may lead to increased morbidity and mortality [40,41]. The use of ECMO prior to cardiovascular collapse in the majority of our patients may have led to improved overall survival.…”
Section: Discussionmentioning
confidence: 95%
“…Attempting to initiate ECMO during cardiac arrest is difficult as it requires pauses in CPR in order to cannulate and initiate the procedure. Prolonged CPR with periods without effective chest compressions may lead to increased morbidity and mortality [40,41]. The use of ECMO prior to cardiovascular collapse in the majority of our patients may have led to improved overall survival.…”
Section: Discussionmentioning
confidence: 95%
“…4 In an out-of-hospital cardiac arrest, Christenson and colleagues observed an improved survival to discharge in patients who received a higher chest compression fraction, i.e., fewer interruptions in chest compressions. 7 In this study survivors also received mean chest compression rates above 110 min -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by Christenson et al provided evidence to suggest that patients with an initial rhythm of ventricular fibrillation or ventricular tachycardia who had higher CCF (>61%) were more likely to achieve return of spontaneous circulation (ROSC) and survive to hospital discharge. 15 Vaillancourt et al conducted a similar investigation on the effects of CCF on patients with a presenting rhythm of asystole or pulseless electrical activity and found that patients with CCFs greater than 81% had the highest probability of obtaining ROSC. 16 …”
Section: Chest Compression Fractionmentioning
confidence: 99%